THE IMAGE OF HISTORICAL FIGURES IN THE NOVEL BY Kh. YESSENZHANOV - AMANGALIEVA, A.E.; SOYLEMEZ, O. (Khoja Ahmed Yasawi International Kazakh-Turkish University, 2023)
The article examines the relevance and significance of historical personalities and events in the trilogy “Aq Zhaiyk” by Hamza Iksanuly Yesenzhanov, a painter who contributed his handwriting to the twentieth century literature in the history of Kazakhstan. The history of October revolution in West Kazakhstan Region is described in comparison with the events presented in the trilogy. The first book is “About the Revolution”, the second book is “Strengthening”, and the third book is the trilogy “Degtyariy Period”, is devoted to the life of historical figures, who took part in the revolution, and it defines the mastery of the writer, who was able to combine the reality of life with the reality of art. The author wrote the trilogy from March 1918 to February 1919 in three books, a trilogy of six parts, fifty chapters and one hundred and eighty-two episodes. The relevance of the study reveals the historical reality of the trilogy, which weighs up the country's history in an unforgettable way, and shows how the reality of life overlaps the reality of art. The scientific significance of the research work will highlight how the “Aq Zhaiyk” trilogy was written. The lives of individuals who took an active part in the historical events based on the trilogy will be revealed. The research material is taken from Khamza Yesenzhanov’s trilogy “Aq Zhaiyk”, from the book “The turbulent years” by the famous revolutionary figure G. Churin, and from history textbooks and archival materials. The results obtained at the end of the study suggest that the features of historical heritage found in folk prose are deterministic.